Osteogenesis of Heterotopically Transplanted Mesenchymal Stromal Cells in Rat Models of Chronic Kidney Disease. (December 2013) - Kramann, Rafael; Kunter, Uta; Brandenburg, Vincent M; Leisten, Isabelle; Ehling, Josef; Klinkhammer, Barbara M; Knüchel, Ruth; Floege, Jürgen; Schneider, Rebekka K
ABSTRACT The current study is based on the hypothesis of mesenchymal stromal cells (MSCs) contributing to soft‐tissue calcification and ectopic osteogenesis in chronic kidney disease (CKD). Rat MSCs were transplanted intraperitoneally in an established three‐dimensional collagen‐based model in healthy control animals and two rat models of CKD and vascular calcification: (1) 5/6 nephrectomy + high phosphorus diet; and (2) adenine nephropathy. As internal controls, collagen gels without MSCs were transplanted in the same animals. After 4 and 8 weeks, MSCs were still detectable and proliferating in the collagen gels (fluorescence‐activated cell sorting [FACS] analysis and confocal microscopy after fluorescence labeling of the cells). Aortas and MSC‐containing collagen gels in CKD animals showed distinct similarities in calcification (micro–computed tomography [µCT], energy‐dispersive X‐ray [EDX] analysis, calcium content), induction of osteogenic markers, (ie, bone morphogenic protein 2 [BMP‐2], Runt related transcription factor 2 [Runx2], alkaline phosphatase [ALP]), upregulation of the osteocytic marker sclerostin and extracellular matrix remodeling with increased expression of osteopontin, collagen I/III/IV, fibronectin, and laminin. Calcification, osteogenesis, and matrix remodeling were never observed in healthy control animals and non‐MSC–containing collagen gels in all groups. Paul Karl Horan 26 (PKH‐26)‐labeled, 3G5‐positive MSCs expressed Runx2 and sclerostin in CKD animals whereas PKH‐26‐negative migrated cells did not express osteogenic markers. In conclusion, heterotopically implanted MSCs undergo osteogenic differentiation in rat models of CKD‐induced vascular calcification, supporting our hypothesis of MSCs as possible players in heterotopic calcification processes of CKD patients. © 2013 American Society for Bone and Mineral Research.